Jedida's work contains a mistake in Step 1.
The original equation is given as:
\[ x^2 - 96 = 4x \]
To rewrite it in standard form \(ax^2 + bx + c = 0\), you would need to set it equal to zero. The correct transformation should be:
\[ x^2 - 4x - 96 = 0 \]
Instead, Jedida wrote:
\[ x^2 + 4x - 96 = 0 \]
This is incorrect because she incorrectly added \(4x\) to the left side of the equation, leading to the wrong quadratic equation.
Thus, the first mistake occurred in Step 1, where she incorrectly set up \(x^2 + 4x - 96 = 0\). The correct setup should have been \(x^2 - 4x - 96 = 0\).